Long-Term Effect of Lactation on Maternal Cardiovascular Function and Adiposity in a Murine Model - Herrera, Sandra R.; Vincent, Kathleen L.; Poole, Aaron; Olson, Gayle; Patrikeev, Igor; Saada, Jamal; Gamble, Phyllis; Motamedi, Massoud; Saade, George R.; Stuebe, Alison M.; Bytautiene Prewit, Egle (American Journal of Perinatology, 2019)
Objective Epidemiological studies suggest that lactation is associated with long-term maternal health benefits. To avoid confounders in human studies, we used a previously characterized murine model to investigate the long-term effect of lactation on both cardiovascular function and adiposity.Study Design After the delivery of the pups, CD-1 female mice were randomly divided into two groups: lactated and nonlactated (NL). Before pregnancy and at 9 months postdelivery, blood pressure was measured using a tail cuff, visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) were assessed by computed tomography (CT), echocardiography was performed using microultrasound, and cholesterol panels and fasting blood glucose were measured. The data were analyzed using Student's t-test (significance at p < 0.05).Results There were no differences in baseline parameters between the two groups. At 9 months postdelivery, the NL group weighed significantly more (p = 0.03) and demonstrated a significantly lower cardiac output (p = 0.05) and ejection fraction (p = 0.03). The mice in the NL group also had higher VAT (p < 0.01) and SAT percentiles (p = 0.03). Fasting glucose (p = 0.01) and low-density lipoprotein (p = 0.01) were significantly higher in the NL group at 9 months.Conclusion Our results show the benefit of lactation is not just limited to the immediate postpartum period but it also extends into midlife in a murine model.
Keywords: adipose tissue; blood pressure; CD-1 mice; lactation; long-term effect